The Influence of Teachers of EnglishWritten Feedback on the Eleventh Graders' Performance in Writing Skill in Salfit District / Experimental Study - Saeed Mohammad Mosa Abu Zir (My University, 2016)
This study aimed to discuss "The Influence of Teachers of English Written Feedback on the Eleventh Graders' Performance in Writing Skill in Salfit District". To achieve this, the researcher used a writing test. This test was applied to (60) male and female students from eleventh graders, divided into two groups, (30) students in each group. The students are from DeriBallut public school in Salfit .The researcher distributed the writing pretest on the control and the experimental groups. The same sample was used to answer the posttest for the same groups after teaching the students in the experimental group how to get benefit from the written feedback strategy. One of the major findings was that students in general had positive results concerning the improvement of writing skills after using written feedback . In the light of this finding, the researcher recommended the extension of applying written feedback for all students in schools. In addition, textbooks' designers should highlight the inclusion of written feedback after each writing activity.

تهدف هذه الدراسة لمناقشة أثر استخدام التغذية الراجعة المكتوبة في تحسين المهارات الكتابية لدى الطلبة الصف الحادي عشر. ولتحقيق هذا الغرض قام البحث باستخدام اختبار كتابي يطبق على 60 طالب من الصف الحادي عشر موزعين على مجموعتين؛ ضابطة و تجريبية. تحتوي كل مجموعة على 30 طالب، حيث قدم الباحث الاختبار القبلي لجميع الطلبة بغية اتمام المعلومات اللازمة لتحقيق غرض الدراسة كما وقام الباحث بتطبيق استراتيجية التغذية الراجعة المكتوبة على طلبة المجموعة التجريبية لقياس اثر هذه الاسترتيجية. ومن ضمن النتائج المتعلقة بالاختبار، فقد لوحظ وجود اثر ايجابي في استخدام استراتيجية التغذية الراجعة المكتوبة في تحسين مهارات الكتابة لدى طلبة المدارس. في ضوء نتائج الدراسة, اوصى الباحث بتكثيف تطبيق استراتيجية التغذية الراجعة المكتوبة على جميع الطلبة في المدارس.بالإضافة لذلك,على مصممي الكتب المدرسية تلسيط الضوء على تضمين استراتيجية التغذية الراجعة المكتوبة بعد كل مهارة كتابة.
أثر التغذية الراجعة المكتوبة المقدمة من معلمي اللغة الانجليزية على أداء طلاب الصف الحادي عشر في مهارة الكتابة في منطقة سلفيت / دراسة تجريبية